Rh(III)‐Catalyzed Divergent C2‐carboxymethylation of Indoles and C7‐formylmethylation of Indolines with Vinylene Carbonate. Issue 10 (27th September 2021) - Hu, Weinan; Wang, Xu; Yu, Xiaoni; Zhu, Xinju; Hao, Xin‐Qi; Song, Mao‐Ping
Abstract: A Rh‐catalyzed divergent alkylation of indole derivatives with vinyl carbonate was described. Depending on the substrate and solvent, indoles reacted with vinyl carbonate and alcohols to give C2 carboxymethylated adducts via a sequential three‐component reaction, while indolines reacted with vinyl carbonate in toluene to provide C7 formylmethylated products. The structures of carboxymethylated product 3 a and formylmethylated product 5 a were further confirmed by X‐ray analysis. The current protocol featured broad substrate scope, tunable reaction conditions, divergent functionalization, and good regioselectivity. Abstract : A Rh‐catalyzed C2‐carboxymethylation of indoles in alcohols and C7‐formylmethylation of indolines in toluene with vinylene carbonate has been successfully developed.